2020
DOI: 10.1021/acs.chemrestox.0c00164
|View full text |Cite
|
Sign up to set email alerts
|

Microcystins: Biogenesis, Toxicity, Analysis, and Control

Abstract: Microcystins are cyclic peptide toxins formed by cyanobacteria. These toxins are recognized for their association with algal blooms, posing a significant threat to ecosystems and drinking water quality. Due to the growing environmental concerns they raise, a comprehensive review on microcystins' genesis, toxicity, and analytical methods for their quantitative determination is outlined. Genes, including the mcyABC cluster, regulate microcystin biogenesis. Bioanalytical experiments have identified key environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 170 publications
0
19
0
1
Order By: Relevance
“…A strong interaction was found between MC-RR with the selenoprotein thioredoxin reductase TRXR1, which regulates the p53 activity and has a high metastatic potential [66,67]. Alteration of TRXR1 levels or activity is accompanied by pro-oxidative changes in the cell, inducing increased oxidative stress, and thus, damage to different biomolecules [66,68].…”
Section: Cellular Proliferation and Cancermentioning
confidence: 99%
“…A strong interaction was found between MC-RR with the selenoprotein thioredoxin reductase TRXR1, which regulates the p53 activity and has a high metastatic potential [66,67]. Alteration of TRXR1 levels or activity is accompanied by pro-oxidative changes in the cell, inducing increased oxidative stress, and thus, damage to different biomolecules [66,68].…”
Section: Cellular Proliferation and Cancermentioning
confidence: 99%
“…Microcystins are hepatotoxins composed of a cyclic heptapeptide with more than 100 isoforms with different toxicities (Puddick, et al, 2014). Being produced by several genera of cyanobacteria, including Microcystis and Anabaena (Schreidah, et al, 2020). These toxins are considered to be very potent and widely distributed cyanotoxins, occurring worldwide.…”
Section: Microcystin and Oxidative Stressmentioning
confidence: 99%
“…61 Previous studies have reported MC-LR altered expression of liver cytochrome P450 (e.g., CYP 2E1) in mice, suggesting a possible involvement of the enzyme with its metabolism. 62 Therefore, a metabolism activation package (MAP) was included in the hydra assay. MAP was standardized and consisted of 2.4 μg/mL mice hepatic microsomal cytochrome P450, 225 μM NADPH, and 25 μM MgCl 2 .…”
Section: Hydra Assaymentioning
confidence: 99%